Patterns of microbiome composition in tsetse fly Glossina palpalis palpalis during vector control using Tiny Targets in Campo, South Cameroon - Calmes Ursain Bouaka Tsakeng; Tito Tresor Melachio Tanekou; François Sougal Ngambia Freitas; Inaki Tirados; Jean Marc Tsagmo Ngoune; Jude Daiga Bigoga; Flobert Njiokou; Charles Sinclair Wondji (Microbiology Spectrum)
ABSTRACT Novel vector control tools against African trypanosomiases require a deep understanding of the factors driving tsetse vector fitness or population resilience in their ecosystems. Following evidence of microbiota-mediated host fitness or traits shaping, including insecticide resistance in arthropod populations, we undertook a comparative study of the microbiota in wild-caught tsetse flies during vector control with deltamethrin-impregnated traps called Tiny Targets. The bacterial microbiome composition of tsetse flies collected before and after 6, 12, and 18 months of vector control were characterized using high-throughput sequencing of the V3-V4 hypervariable region of the bacterial 16S rRNA gene and compared. Overall, 48 bacterial genera and five phyla were identified. The primary symbiont Wigglesworthia dominated almost all the samples with an overall relative abundance of 71.76%. A significant increase was observed in microbiome diversities over the vector control with new taxa identified. Interestingly, few genera, like Curvibacter for instance, displayed a regularly increasing abundance, from 0.57% to 0.65%, 4.73%, and 8.57% after 6, 12, and 18 months of tsetse control, respectively. This study provided preliminary for further investigation into the role and mechanism of action of microbiota in tsetse fly fitness under selective pressure like insecticides.IMPORTANCEThe interest in vector control in the fight against African trypanosomiases has been reinforced in recent years, with the development of small insecticide-impregnated screens, known as “Tiny Targets”. As some tsetse biotopes are difficult to access for their installation, other tools are under consideration that involve using bacteria harbored by the tsetse vector to block the development of trypanosomes or impair the tsetse’s fitness in its natural environment. Several bacterial symbionts were previously described as important for tsetse fly development, and some like Burkholderia and Citrobacter also found in tsetse flies were found associated with insecticide tolerance in other arthropods. In this research, we found the bacterial genera, Curvibacter and Acinetobacter, increased in abundance in tsetse flies during vector control. These bacteria deserve further attention to determine if they can interfere with insecticides used to control tsetse fly populations.